Pengaruh Penambahan Electrical Muscle Stimulation (EMS) Peningkatan Tonus Otot Pada Penderita DD - Agus Widodo; BJ. Zia Yucca Praditya (Universitas Muhammadiyah Surakarta, 2013)
Delayed Development (DD) is the classification of characteristics of children which is showeda significant delay in one or more domains of cognitive development, emotional or physical. The problemsthat arise in the DD are hypotonus of the muscles that cause delays in functional abilities ofchildren.The purpose of this study was to determine the influence of Electrical Muscle Stimulation(EMS)to increase muscle tone of DD patients. Quasi-experimental research method using two pre andpost-testgroup design. Sample of this research was 12 children 1-3 years of age. Measurement ofmuscletone using a sphygmomanometer before and after treatment for 4 weeks. The effect measuredusing Wilcoxon tes and the different effect measured using Mann Whitney test. Wilcoxon test resultshowedthat the effect of electrical muscle stimulation on muscle tone was seen from the right quadricepsp value (p = 0.026), the left quadriceps (p = 0.024), right tibialis anterior (p = 0.024) and left tibialisanterior(p = 0.024). It can be concluded that there is an effect of Electrical Muscle stimulation onincreasingthe muscle tone in people with DD.